The influence of financial literacy on investment decisions of Jakarta Global University students - Rahmawati Ulfah (Universitas Pendidikan Nasional, 2022)
By understanding the influence of financial literacy on the investment decisions of JGU students, it was possible to identify specific measures that could be taken by universities, financial institutions, and the government to enhance financial awareness and the quality of investment decision-making among students. According to the survey, Indonesia's financial literacy level was comparatively lower than that of neighbouring countries, especially in the field of students. The purpose of this research was to determine the influence of financial literacy on investment decisions among students at Jakarta Global University and to assess the extent of its impact. The model of analysis in this study used the Structural Equation Model (SEM), and the tool employed was the SmartPLS 2.0 M3 program. The results of hypothesis testing and discussion showed that financial literacy had a significantly positive influence on the investment decisions of JGU students. This result indicated that students with higher levels of financial literacy tended to make wiser and more informed investment decisions compared to those with lower levels of financial literacy.